Online English Language Teaching: technological tools and online methods - Majano Arias, Efraín; Sánchez Canizalez, Tania Mayeli; Meza Guevara, Heisy Saray (2024)
A learning management system (LMS) is a type of software or technology supported online that allows you to create, implement and develop a training program or a specific learning process. That is the main purpose of this specialization course: “Administration of Virtual Environments for the Teaching and Learning of Foreign Languages” that teaches about the theoretical fundamentals and the use of technological tools for teaching-learning a foreign language in a virtual modality, in which the students had learned in a total of three modules the importance, the use, the advantages and disadvantages of using a learning management system in the virtual environment. There is a brief explanation about the different technological tools that were taught to the students and then can be found in specific explanations of activity that were developed by the students in the modules. Also, a short summary of what was learned during the specialization course, as well as all the activities done individually and in groups is presented. Key words: Asynchronous learning ; E-learning ; LMS (Learning Management System) ; Synchronous learning ; Technological tools.